FERMENTATION OF WHEY WASTE AS ORGANIC LIQUID FERTILIZER "PUCAFU" - Muhammad Akhsan Akib; Henny Setiawati (Agrotech Journal, 2017)
Whey waste contains organic materials, particularly high complex proteins and amino acids in the form of suspended and dissolved solids, however the utilization of whey as a organic liquid fertilizer still has a less attention. Thus the Utilization of the whey waste through anaerobic process to be used as a organic liquid fertilizer is the purpose of the research. This research was conducted using factorial design with completely randomized design (CRD) which consists of two factors: the yeast concentration (without yeast; 0.25 and 0.50 g/500 ml of whey waste) and the fermentation time (0, 3, and 5 days). The variables measured were the content of organic C, C/N Ratio, and Total N, P2O5 and K2O contents. The results showed that the fermented whey waste on the different fermentation time and yeast concentration had increased the organic C and C/N ratio, but decreased P2O5 and K2O contents. The utilization of whey combined with solid or other liquid wastes gave a chance to produce a quality organic liquid fertilizer